The Evaluation of Service Quality For M-Gov: A Conceptual Framework Building by Extant Review - Anas A. Salameh (International Journal of Supply Chain Management, 2020)
Citizens’ perceiving m-government service quality has become a large challenge for the improvement of m-government in Jordan. This research has produced a model m-government service quality, the perceived service quality on m-government context upon citizens' trust and their willingness to use it, little attention has been given to examining the perceived service quality which contributed by m-government from citizens' perspective. This paper presents a systematic and analytical review of the contemporary literature on citizens’ perceiving m-government SQ, with a singular focus on the common critical factors affecting citizens toward m-government SQ. The prior literature was recognized through eight well-known journals, from 2004 to 2017. Academic studies were examined if they contained a relevant discussion of the antecedents or factors influencing citizens’ perceptions in the m-government context. This research supports the elements of m-government service quality by (PLS) analysis and then examines the proposed conceptual model using modeling of the structural equation. The conclusions of the study present that the concept of m-government service quality has three relevant dimensions: ease of use, trust, and web design are positively correlated with the m-government service quality.